2006
DOI: 10.1520/jai12817
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium and Niobium Affect Human Osteoblasts, Fibroblasts, and Lymphocytes in a Similar Manner to More Traditional Implant Alloy Metals

Abstract: Implant debris remains the major factor limiting the longevity of total joint replacements. Whether soluble implant debris of Zr and Nb containing implant alloys constitute a greater risk than other implant metals remains unknown. We evaluated the relative effects of soluble forms of Zr+4 and Nb+5 (0.001–10.0 mM) relative to Cr+3, Mo+5, Al+3, Co+2, Ni+2, Fe+3, Cu+2, Mn+2, Mg+2, Na+2, and V+3 chloride solutions on human peri-implant cells (i.e., osteoblast-like MG-63 cells, fibroblasts, and lymphocytes). Metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Early studies demonstrated that below 0.01 mM, neither Zr nor Mo was toxic to osteoblasts and fibroblasts. 5,55 In addition, the biocompatibility of Zr-Mo alloys was primarily evaluated by culturing L-929 cells and MG 63 cells in their extraction media and positive results were obtained, indicating an excellent in vitro biocompatibility.…”
Section: Biocompatibility Of Zr-mo Alloys and Their Promises As Medicmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies demonstrated that below 0.01 mM, neither Zr nor Mo was toxic to osteoblasts and fibroblasts. 5,55 In addition, the biocompatibility of Zr-Mo alloys was primarily evaluated by culturing L-929 cells and MG 63 cells in their extraction media and positive results were obtained, indicating an excellent in vitro biocompatibility.…”
Section: Biocompatibility Of Zr-mo Alloys and Their Promises As Medicmentioning
confidence: 99%
“…[1][2][3] Zirconium has been recognized to be nontoxic and nonallergic. 4,5 In vivo evidences showed that zirconium implants exhibited good osseointegration and even a higher degree of bone-implant contact than titanium implants. 6,7 By bioactive surface modifications such as NaOH treatment 8 and sol-gel method, 9 a bone-like apatite layer could form on the surface of Zr metal, through which the implant bonds to bone.…”
Section: Introductionmentioning
confidence: 99%
“…In the in vitro setting, Rogers and colleagues 10 were able to show that Ti-6Al-4V activates monocytes and induces the release of the inflammatory mediator prostaglandin E2 (PGE2) to a greater extent than does Ti-6Al-7Nb. This discrepancy may result from the fact that niobium is less toxic to cells than vanadium, as has been recently verified by Hallab and colleagues 11 using cell proliferation and viability tests. Recently, Wooley and coworkers 12 demonstrated that Ti6Al-4V particles implanted into the murine air pouch-model caused a reactive membrane inflammation, probably mediated by interleukin-6.…”
Section: Introductionmentioning
confidence: 89%
“…[7][8][9] Both constituents of these alloys have been separately proven to be biocompatible, and they have received considerable attention from researchers working in the biomaterials field due to the superior corrosion resistance they exhibit. [7][8][9] Recent works on this material have demonstrated that an excellent combination of mechanical properties, high strength, and good fatigue resistance can be obtained in NbZr alloys upon introduction of an ultrafine-grained (UFG) microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Both constituents of these alloys have been separately proven to be biocompatible, and they have received considerable attention from researchers working in the biomaterials field due to the superior corrosion resistance they exhibit. [7][8][9] Recent works on this material have demonstrated that an excellent combination of mechanical properties, high strength, and good fatigue resistance can be obtained in NbZr alloys upon introduction of an ultrafine-grained (UFG) microstructure. [10][11][12][13] For implant materials, in addition to resistance against corrosion induced by the chemically aggressive human body environment, mechanical performance related parameters, such as high strength, improved fatigue resistance, and fracture toughness, are also important, especially considering loading conditions that can sometimes become intense.…”
Section: Introductionmentioning
confidence: 99%